Analysis of Dental Enamel Surface Submitted to Fruit Juice Plus Soymilk by Micro X-Ray Fluorescence: In Vitro Study - Janaína Salmos Brito; Alexandrino Santos Neto; Luciano Silva; Rebeca Menezes; Natália Araújo; Vanda Carneiro; Lara Magalhães Moreno; Jéssica Miranda; Pâmella Álvares; Giselle Nevares; Felipe Xavier; José Alcides Arruda; et al. (The Scientific World Journal)
Objective. This paper aimed to analyze the in vitro industrialized fruit juices effect plus soy to establish the erosive potential of these solutions. Materials and Methods. Seventy bovine incisors were selected after being evaluated under stereomicroscope. Their crowns were prepared and randomly divided into 7 groups, using microhardness with allocation criteria. The crowns were submitted to the fruit juice plus soy during 15 days, twice a day. The pH values, acid titration, and Knoop microhardness were recorded and the specimens were evaluated using X-ray microfluorescence (µXRF). Results. The pH average for all juices and after 3 days was significantly below the critical value for dental erosion. In average, the pH value decreases 14% comparing initial time and pH after 3 days. Comparing before and after, there was a 49% microhardness decrease measured in groups (p<0.05). Groups G1, G2, G5, and G6 are above this average. The analysis by μXRF showed a decrease of approximately 7% Ca and 4% P on bovine crowns surface. Florida (FL) statistical analysis showed a statistically significant 1 difference between groups. Thus, a tooth chance to suffer demineralization due to industrialized fruit juices plus soy is real.